Odpowiedzi

2009-12-20T18:50:15+01:00
Usuń ten post, nei mgoe dodac zalącznika, sorki
2009-12-20T18:53:15+01:00
D)
4x-5y=-4
-2x+3y=1.1 I*2

4x-5y=-4
-4x+6y=2,2

y=-1,8

4x-5y=-4
y=-1,8

4x-5*(-1,8)=-4
y=-1,8

4x-9=-4
y=-1,8

4x=-4+9
y=-1,8

4x=5 /:4
y=-1,8

x=1,25
y=-1,8

e)
-2x+y=0 I*3
3x-3y=1

-6x+3y=0
3x-3y=1

-3x=1 /:(-3)
x=-1/3

3x-3y=1
x=-1/3

3*(-1/3)-3y=1
x=-1/3

-1-3y=1
x=-1/3

-3y=1+1
x=-1/3

-3y=2 /:(-3)
x=-1/3

y=-2/3
x=-1/3

f)
3x-2y=-12 I*(-2)
2x-5y=-19 I*3

-6x+4y=24
6x-15y=-57

-11y=-33 /:(-11)
y=3

-6x+4y=24
y=3

-6x+4*3=24
y=3

-6x+12=24
y=3

-6x=24-12
y=3

-6x=12 /:(-6)
y=3

x=2
y=3